2013
DOI: 10.1096/fj.12-218727
|View full text |Cite
|
Sign up to set email alerts
|

Differential targeting of the dopamine transporter to recycling or degradative pathways during amphetamine‐ or PKC‐regulated endocytosis in dopamine neurons

Abstract: The dopamine transporter (DAT) clears the extracellular dopamine released during neurotransmission and is a major target for both therapeutic and addictive psychostimulant amphetamines. Amphetamine exposure or activation of protein kinase C (PKC) by the phorbol ester PMA has been shown to down-regulate cell surface DAT. However, in dopamine neurons, the trafficking itinerary and fate of internalized DAT has not been elucidated. By monitoring surface-labeled DAT in transfected dopamine neurons from embryonic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 40 publications
(48 reference statements)
5
65
0
Order By: Relevance
“…However, in naive animals, a single amphetamine infusion decreased DAT membrane expression and V max , demonstrating that amphetamine effects on these endpoints are substantially modulated by previous experience with cocaine. Although membrane expression of the DAT as measured by western blotting in the current investigation is not necessarily indicative of DAT cell-surface expression per se, a reduction in membrane expression following amphetamine infusion in naive animals is consistent with a large body of literature on amphetamine-induced DAT internalization (Fleckenstein et al, 1997(Fleckenstein et al, , 1999Saunders et al, 2000;Boudanova et al, 2008;Richards and Zahniser, 2009;Hong and Amara, 2013). Indeed, previous studies have reported substrate-induced downregulation of surface DAT expression anywhere from 1 min to hours after administration in cultured cell models or in synaptosomes (Fleckenstein et al, 1999;Saunders et al, 2000;Richards and Zahniser, 2009).…”
Section: Discussionsupporting
confidence: 86%
“…However, in naive animals, a single amphetamine infusion decreased DAT membrane expression and V max , demonstrating that amphetamine effects on these endpoints are substantially modulated by previous experience with cocaine. Although membrane expression of the DAT as measured by western blotting in the current investigation is not necessarily indicative of DAT cell-surface expression per se, a reduction in membrane expression following amphetamine infusion in naive animals is consistent with a large body of literature on amphetamine-induced DAT internalization (Fleckenstein et al, 1997(Fleckenstein et al, , 1999Saunders et al, 2000;Boudanova et al, 2008;Richards and Zahniser, 2009;Hong and Amara, 2013). Indeed, previous studies have reported substrate-induced downregulation of surface DAT expression anywhere from 1 min to hours after administration in cultured cell models or in synaptosomes (Fleckenstein et al, 1999;Saunders et al, 2000;Richards and Zahniser, 2009).…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, this AMPH effect did not require the C-terminal FREKL motif necessary for PKC-stimulated DAT trafficking (Boudanova et al, 2008). In the work by Hong and Amara (2013) in rat primary DA neurons mentioned above, AMPH treatment led to colocalization of DAT with early/recycling endosomes and not late-endosomes/ lysosomes as was seen with PMA treatment. The Amara laboratory recently provided evidence that AMPHtriggered DAT endocytosis is clathrin-independent and requires the small GTPase Rho (Wheeler et al, 2015), which mediates another dynamin-dependent mode of endocytosis (Croise et al, 2014).…”
Section: Regulation Of Dopamine Transporter Membranementioning
confidence: 80%
“…The fate of b-PMA-stimulated internalized DAT also appears to differ from DAT that is constitutively endocytosed. In both hDAT-HEK-293 cells and rat primary DA neurons, treatment with b-PMA leads to colocalization of DAT with markers of late endosomes/ lysosomes, whereas DAT that is constitutively endocytosed colocalizes mostly with markers of early/recycling endosomes (Hong and Amara, 2013). It should be noted that a conflicting study also looking at rat primary DA neurons found no effect of PMA on DAT internalization (Eriksen et al, 2009), although at present the basis for these contradicting findings is unclear.…”
Section: Regulation Of Dopamine Transporter Membranementioning
confidence: 94%
See 1 more Smart Citation
“…However, there appear to be subtle differences between PKC-dependent and AMPH-dependent DAT internalization. Both AMPH and PKC activation results in loss of cell surface DAT in vitro, but contrary to the PKC-induced internalization that is dependent on DAT ubiquitination and subsequent sorting to LAMP1-positive endosomes for degradation, the AMPH-induced internalization sorted the DAT to Rab11-positive recycling endosomes (Hong and Amara, 2013), likely destined to be quickly reinserted into the membrane.…”
Section: Regulation Of Dopamine Efflux Via the Dopamine Transporter Bmentioning
confidence: 92%